PERSEPSI DAN EKSPEKTASI PESERTA DIDIK TERHADAP PELAKSANAAN LAYANAN KLASIKAL DI SMAK ABDI WACANA PONTIANAK TAHUN 2019/2020 - Rosmela Dwi Utari; Yuline Yuline; Indri Astuti (Universitas Tanjungpura, 2020)
AbstractThe classification of Guidance is called a basic service in Guidance and Counseling Because the rating Guide is the part that picks the biggest portion flat service Counseling at school. Various perceptions and expectations that arise in students both positive and negative perception greatly affect the results, interests and attitudes of learning so as to create an impression in receiving lessons. The general problem in this study is